Waste evaluation in chocolate powder production using a lean manufacturing approach - Jessica Vyanti; Muhammad Kusumawan Herliansyah (Jurnal Teknosains, 2026)
Nglanggeran Village, located in Gunungkidul Regency, Yogyakarta, has substantial potential for the development of the local cocoa industry. Cocoa production in this village is integrated and managed by Griya Cokelat Nglanggeran, a community-based enterprise that focuses on processing cocoa beans into various derivative products. Despite its strong potential, the production process still faces several inefficiencies, particularly in the cocoa powder manufacturing stage. These inefficiencies hinder productivity and reduce overall process effectiveness. To address these challenges, this study applies the Lean Manufacturing approach, which emphasizes waste reduction and value enhancement throughout the production chain. Specifically, the research utilizes Value Stream Mapping (VSM) and Process Activity Mapping (PAM) to systematically visualize the production flow, identify non-value-added (NVA) activities, and analyze existing sources of waste. In addition, Fishbone Diagram, Failure Mode and Effect Analysis combined with Simple Additive Weighting (FMEA-SAW), and Fault Tree Analysis (FTA) are employed to trace the root causes of inefficiencies and propose prioritized improvement strategies based on risk levels. The findings indicate that, of the entire set of observed production activities, 196 were classified as waste, while only 24 contributed direct value. Among the seven types of waste, motion and transportation were identified as the most dominant, leading to the need for improvements in workspace layout and material handling management. After implementing corrective measures derived from the analytical results, the total duration of NVA activities decreased significantly from 3,059,830 seconds to 261,301 seconds, representing a 76.98% improvement in process efficiency relative to the total production time. These findings demonstrate that the application of Lean Manufacturing tools can significantly optimize cocoa powder production at Griya Cokelat Nglanggeran, while also providing a feasible model for other small-scale agro-industry enterprises seeking sustainable operational efficiency.